2004
DOI: 10.1159/000078994
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoamniotic Shunts: Fetal Treatment of Pleural Effusions and Congenital Cystic Adenomatoid Malformations

Abstract: Objective: To determine whether fetuses that underwent thoracoamniotic shunt placement for treatment of pleural effusion (PE) or macrocystic congenital cystic adenomatoid malformation (CCAM) have an improved outcome as compared with an untreated population. Methods: A retrospective review from a single tertiary center was performed using thoracoamniotic shunt placement to treat PE or macrocystic CCAM between 1998 and 2001. Thoracoamniotic shunts were used on 26 occasions in 19 pregnancies. Results: The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 31 publications
5
72
3
5
Order By: Relevance
“…4 In the present case, we decided to place this shunt at 33 weeks because we observed that the cyst had developed recently and acutely and that it was responsible for severe mediastinal shift leading to polyhydramnios and preterm labor. Our first procedure gave a good result for one week.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…4 In the present case, we decided to place this shunt at 33 weeks because we observed that the cyst had developed recently and acutely and that it was responsible for severe mediastinal shift leading to polyhydramnios and preterm labor. Our first procedure gave a good result for one week.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that, at a later stage, a better therapeutic option might be prenatal puncturing of the adenomatoid cyst. 4 However, multiple punctures might be needed, which might increase the risks of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los fetos con lesiones con un quiste dominante en los cuales se desarrola hidrops antes de las 32 semanas de gestación, pueden ser consideradas para tratamiento en útero con drenajes toracoamnióticos, con resultados que alcanzan el 70% de sobrevida 13 . En los casos de lesiones microquisticas grandes con desarrollo de hidrops antes de las 32 semanas, y que no mejoran con la administración materna de esteroides, se debería considerar toracotomía fetal para resección de la lesión (figura 1).…”
Section: Lesiones Pulmonares Fetalesunclassified